VO2 peak provides a better predictor of ergometer mean maximal power than maximal oxygen extraction in trained rowers - Lanigan, B.; Tinely, Z. L.; Binnie, M. J.; Peeling, P.; Scott, B. R.; Peiffer, J. J.; Galna, B.; Dennis, M. C.; Billaut, F.; Goods, P. S. R. (Journal of Clinical Exercise Physiology, 2024)
INTRODUCTION & AIMS Muscle oxygenation characteristics are suggested to better explain performance than peak oxygen uptake (VO2peak) in highly trained canoe-kayak athletes (Paquette et. al, 2018), but this has not been explored with rowers. Therefore, this investigation aimed to 1) determine whether maximal oxygen extraction improved prediction of rowing ergometer mean maximal power (MMP; W/kg) compared to VO2peak alone, and 2) assess differences in muscle oxygen extraction between anatomical sites during incremental rowing.